'This untranslatability which is not one'. Issue 2 (July 2015) - Lezra, Jacques
<x xml:space="preserve">Abstract</x> Translatability in natural languages today supports, and can only be understood in the context of, economic globalization, and the universalization of market logic. 'Untranslatability', as it is most often construed, does not provide a critical alternative to this logic: it bolsters it. A different account of untranslatability (and, by extension, of what it means for expressions in natural languages to be 'translatable') is required: this essay seeks to provide such. It finds in passages in Marx and in Derrida's Monolinguisme de l'autre, and in different translations of those texts, an untranslatability which is not one, irreducible to mathematical identity.